The near-complete mitogenome of the critically endangered Pseudocleopatra dartevellei (Caenogastropoda: Paludomidae) from the Congo River assembled from historical museum material. Issue 2 (3rd July 2019) - Stelbrink, Björn; Kehlmaier, Christian; Wilke, Thomas; Albrecht, Christian
Abstract: Here, we present the first near-complete mitogenome of a member of the freshwater gastropod family Paludomidae, Pseudocleopatra dartevellei . This Congo River species is of particular importance because the sister to the Lake Tanganyika radiation is supposed to be a paludomid riverine species. We used ancient DNA (aDNA) techniques including single-stranded DNA library preparation in order to assemble the mitogenome from historical museum material collected in 1937. The mitogenome was 15, 368 bp long and showed typical characteristics as identified in other freshwater gastropods. The present phylogeny shows a closer relationship between Pseudocleoptra dartevellei and another non-Tanganyikan species, Cleopatra johnstoni .